Study on preparation, photocatalytic performance and degradation mechanism of polymeric carbon nitride/Pt/nano-spherical MoS2 composite. (July 2022) - Fu, Weijie; Zhao, Youhai; Wang, Haiwang; Chen, Xiong; Liu, Kefan; Zhang, Ke; Wei, Qingquan; Wang, Bingzhu
Abstract: In this paper, a visible light-driven polymeric carbon nitride (PCN)/(Pt)/nano-spherical MoS2 photocatalysts was prepared using a self-assembly method. The structure of photocatalysts was explored by FT-IR, XPS, XRD, BET, SEM and TEM. Meanwhile, the energy band structure and electron hole separation efficiency were also analyzed by UV–Vis and PL spectra. In addition, the photocatalytic performance of photocatalysts were tested by photocatalytic degradation of Rhodamine B and photocatalytic hydrogen evolution. The results showed that PCN/2.0%MoS2 showed the best photocatalytic performance, and the degradation rate of Rhodamine B could reach 98.39% within 150 min. Besides, the introduction of Pt nanoparticles significantly improved the photocatalytic activity. The degradation rate of Rhodamine B reached 100% within 150 min, and the rate of photocatalytic hydrogen production of PCN/Pt/MoS2 system was increased by 21.3% over the PCN/2.0%MoS2 system. The separation mechanism of electron and hole is Z-scheme mechanism and the main active substances for photocatalytic degradation were · O 2 − and h + . Graphical abstract: Image 1 Highlights: The catalyst is prepared by self-assembly. Pt promotes the formation of carriers. The transportation of carriers is Z-scheme.